The Kindle : pricing complementary products in a competitive market - Oster, Sharon M., (SAGE knowledge. Cases., 2016)
The Kindle, a portable electronic reading device sold by online retailer Amazon.com, is changing the experience of reading. This study examines the impact of the Kindle on the book business as a whole.